(untitled) (PerCursos, 2022)
Considering the main agro-industrial regions of Brazil, a complex spatial circuit of agro-industrial production of meat and meat products is installed in the West of the state of Santa Catarina, in the southern region of the country, especially aimed at breeding, slaughtering, and processing of poultry and swine. Based on this empirical context, the objective of this work is to describe and analyze the possible relationships between the interiorization of the recent Covid-19 pandemic in Brazil and the specificity of productive activity located in agro-industrial regions, focusing on the theme of circulation and spatial mobility of labor. The methodology included theoretical and thematic bibliographic reviews, data analysis of this theme and varied journalistic materials. As a synthesis of the results achieved, it became evident that as a basis for the dimension of production, the dependence of the agro-industrial sector in relation to the circulation and spatial mobility of labor constitutes a potential scenario of vulnerability to the region specialized in this activity, especially due to the difficulty of constituting adaptations in the face of adversity scenario, such as the one caused by the Covid-19 pandemic.